Newer Substituted β-Aminonaphthalenes as Potent Anti-inflammatory Agents - Bansal, Ekta; Kishor Srivastava, Virendra; Kumar, Ashok (Arzneimittelforschung, 2000)
β-[2-(3’-Chloro-2’-oxo-4’-substituted aryl-1’-azetidinyl)-thiazol-4-yl]aminonaphthalenes 13-17 and β-[2-(1’,3’-disubstitutedphenyl-formazan-4’-yl)-thiazol-4-yl] aminonaphthalenes 8-12 were synthesized from β-(2-arylideneamino-thiazol-4-yl)aminonaphthalenes 3-7 by diazotisation and by cycloaddition with monochloroacetyl chloride, respectively, on the azomethine group of the compounds 3-7. The newly synthesized compounds showed potent anti-inflammatory and analgesic activities and were less ulcerogenic than phenylbutazone.
Keywords: Azetidinyl-thiazolylaminonaphthalenes, acute toxicity studies; anti-inflammatory and analgesic activity, rat, synthesis; Formazanyl-thiazolyl aminonaphthalenes, acute toxicity studies; anti-inflammatory and analgesic activity, rat, synthesis